Assessment of myocardial repolarisation parameters in patients with familial Mediterranean fever - Karaman, Kayıhan; Karayakalı, Metin; Erken, Ertuğrul; Demirtaş, Ahmet; Öztürk, Mustafa; Altunkaş, Fatih; Arısoy, Arif; Turan, Oğuzhan Ekrem; Ceyhan, Köksal; Çelik, Ataç (Cardiovascular Journal of Africa, 2017)
Familial Mediterranean fever (FMF) is a chronic, recurrent auto-inflammatory disease characterised by self-terminating attacks of fever and sterile polyserositis. The main cause of death in auto-inflammatory diseases is cardiovascular events. Additionally, auto-inflammatory diseases have potential effects on the myocardial repolarisation parameters, including the T-wave peak-to-end (Tp-Te) interval, cTp-Te interval (corrected Tp-Te) and the cTp-Te/QT ratio. The aim of this study was to analyse the efficacy of myocardial repolarisation alterations in anticipation of cardiovascular risks in patients with FMF. This study included 66 patients with FMF and 58 healthy control subjects. Tp-Te and cTp-Te intervals and the cTp-Te/QT ratio were measured from the 12-lead electrocardiogram. In electrocardiographic parameters, analysis of QT, QT dispersion, corrected QT (QTc) and QTc dispersion were similar between the groups. The Tp-Te and cTp-Te intervals and Tp-Te/QT and cTp-Te/QT ratios were significantly prolonged in FMF patients. Multivariate linear regression analyses indicated that erythrocyte sedimentation rate was an independent predictor of a prolonged cTp-Te interval. Our study revealed that when compared with control subjects, Tp-Te and cTp-Te intervals and cTp-Te/QT ratio were increased in FMF patients.